Price and Volatility Spillovers in the Electricity Reliability Council of Texas Day-Ahead Electricity Market - Abrokwah, Ama Agyeiwaa (International Journal of Energy Economics and Policy, 2018)
This paper examines price and volatility spillovers in the day-ahead electricity market among the four Hubs in the Electricity Reliability Council of Texas (ERCOT) and the Southwest Power Pool (SPP). Tests of causality and impulse response functions based on a vector autoregressive model suggest cross-market spillovers from SPP to ERCOT hubs, and from North to other hubs. Examination of volatility dynamics using multivariate GARCH-BEKK suggests positively significant own ARCH and GARCH effects in North and South hubs. Examination of conditional correlations using constant conditional correlation and dynamic conditional correlation models suggest high conditional correlations between Houston and South, Houston and North, and South and North; Mid-range correlations between West and other ERCOT hubs; and low correlations between ERCOT hubs and SPP. The findings suggest that the ERCOT ISO will potentially benefit from integration with the SPP as well as improvements in transmission systems from the West to other hubs. Keywords: Electricity Reliability Council of Texas (ERCOT), day-ahead electricity market, volatility spillovers JEL Classifications: C01, C51, L11 DOI: https://doi.org/10.32479/ijeep.7001